Optimasi Desain Crash Box Tipe Square Dengan Beban Impak Arah Aksial - Putrawani, Eky; Akbar, Musthafa (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Crash box is one of the passive security system technology that serves to absorb impact energy when the car suffers a collision. The Crash box has a parameter crashworthiness which is a parameter that indicates the durability of structures to protect a passenger during collision. The crashworthiness parameters in the crash box is energy absorption (EA), primary Peak Force (Pmax), mean crushing force (Pm), crushing force efficiency (CFE), and specific energy absorption (SEA). In this research conducted optimization of the design of the crash box with numerical analysis using software-based finite element method Abaqus CAE ver. 6.14-2. This research was conducted to get the design of the crash box which has the most optimal crashworthiness parameter value of some model of the square type crash box design with an impact load axial direction. The design Model of the crash box is analyzed include adding design modifications using triggers, multi segments, and rib. The selected crash box Material used is Alumunium AA6060-T4. Base on analysis carried out the design model of the crash box with the addition of rib (R06) as a design model that has the most optimal crashworthiness parameters. The R06 design Model increases energy absorption (EA) by 0.02 kJ (0.37%), lowering primary peak force (Pmax) by 10.72 kN (21.16%), increasing mean crushing force (Pm) of 0.11 kN (0.37%), increasing crushing force efficiency (CFE) of 15.81% (27.32%), but lowering the specific energy absorption (SEA) of 0.91 kJ/kg (4.63%). Keyword : Crash Box, Design Optimization, Crashworthiness Analysis